2011
DOI: 10.1186/1471-2415-11-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of visual impairment, cataract surgery and awareness of cataract and glaucoma in Bhaktapur district of Nepal: The Bhaktapur Glaucoma Study

Abstract: BackgroundCataract and glaucoma are the major causes of blindness in Nepal. Bhaktapur is one of the three districts of Kathmandu valley which represents a metropolitan city with a predominantly agrarian rural periphery. This study was undertaken to determine the prevalence of visual impairment, cataract surgery and awareness of cataract and glaucoma among subjects residing in this district of Nepal.MethodsSubjects aged 40 years and above was selected using a cluster sampling methodology and a door to door enum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
60
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 27 publications
11
60
3
1
Order By: Relevance
“…Furthermore, males and those with increased age had greater awareness of glaucoma. Similar findings were reported in another study 11. In contrast to a hospital population study within the same region of this study, those who worked in the ophthalmic unit, and had higher social class had more awareness of eye diseases including glaucoma 8…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, males and those with increased age had greater awareness of glaucoma. Similar findings were reported in another study 11. In contrast to a hospital population study within the same region of this study, those who worked in the ophthalmic unit, and had higher social class had more awareness of eye diseases including glaucoma 8…”
Section: Discussionsupporting
confidence: 88%
“…Similar findings were reported in a Canadian study 10. However this observation is in contrast to findings reported by other authors from Ethiopia11 and Nepal12 where males predominated. The differences between studies may be cultural where women are not allowed to express themselves fully.…”
Section: Discussionsupporting
confidence: 86%
“…A recent population based study conducted in the Bhaktapur district reported that vitreo-retinal diseases were the second major cause of blindness following cataract, while being the most common cause of blindness among pseudophakics [21,22]. This paper will further elaborate the findings from this population based study regarding the prevalence, types and visual impairment from vitreo-retinal disorders in this district.…”
Section: Introductionmentioning
confidence: 75%
“…Various studies in developing/ underdeveloped countries have shown a low rate of awareness, 5,[8][9][10][11] whereas relatively higher level of awareness is reported from developed countries. Various studies in developing/ underdeveloped countries have shown a low rate of awareness, 5,[8][9][10][11] whereas relatively higher level of awareness is reported from developed countries.…”
Section: Introductionmentioning
confidence: 99%